Exploring the health and social care needs of older people with a drug problem. (2nd November 2019) - Matheson, Catriona; Hamilton, Emma; Wallace, Jason; Liddell, David
Abstract: Aim: This study described the healthcare and support needs of ageing and older people with a drug problem in Scotland. Methods: A sample of 123 injecting heroin users, >35 years across Scotland were interviewed by peer researchers, via a purposive sample of non-NHS health and support services. Quantitative data covered demography, drug history, health, service use and relative importance of different health and social issues. Qualitative data covered services and health. Thirty interviews underwent thematic analysis. Results: Participants were 35–57 years old, 76.4% ( n = 94) were male. Of 123 participants, 78.9% lived alone and 91.1% had been homeless at some time. The majority had been in treatment several times with mixed experiences including feeling 'forgotten about'. 75.1% had overdosed during their lives, 95.1% suffered from depression, 88.6% anxiety and 52.8% chronic pain. Mental health problems were rated as important by 92% of participants., Isolation and loneliness emerged as a key theme as did stigma, especially when seeking treatment for comorbidities. Conclusions: This is a very vulnerable group due to their multiple health and support needs. They may be at increased risk of overdose due to poor mental health and isolation. Many lived alone potentially reducing the effectiveness of naloxone programmes. Services need to respond appropriately.